2011
DOI: 10.1021/ef2004915
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preparation Methods and Content of Boron on Hydrotreating Catalytic Activity

Abstract: The effects of boron content and preparation methods are studied in this present investigation. Three different methods are employed for the preparation of catalysts. The catalysts are characterized by pore size distribution (PSD), X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Thiophene hydrodesulfurization (HDS), cumene hydrocracking (HC), gas oil HDS and Maya heavy crude oil HDS, and hydrodemetallization (HDM) activities are tested. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The modulation capability of promoters for catalyst performances is not only relevant to the nature of the promoter itself and quantity of the promoter, but also connected with the impregnation order of active metal and the promoter [18,19,22,50,51] …”
Section: Promotersmentioning
confidence: 99%
See 3 more Smart Citations
“…The modulation capability of promoters for catalyst performances is not only relevant to the nature of the promoter itself and quantity of the promoter, but also connected with the impregnation order of active metal and the promoter [18,19,22,50,51] …”
Section: Promotersmentioning
confidence: 99%
“…To these promoters, The content must be suitable because excessive content of promoter may inversely strengthen the metal-support interaction due to the improvement of the dispersion degree of active phase in this case [50]; third, promoters could achieve the modulation ability through "isolation" of the active metal and support in physical space. For B modified catalyst B-MoNi/ Al 2 O 3 and MoNi-B/Al 2 O 3 [22], the former which impregnated B and MoNi in sequence has better modulation capability than the latter. This is because B (w0.6%) could be monolayer distribution on the carrier surface in B-MoNi/Al 2 O 3 , which "separates" active metal and carrier in some extent and thereby weaken the metal-carrier interaction.…”
Section: Influences On Metal-support Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers also did a lot of studying on the hydrotreating reactors. Maity et al studied the effects of boron content and preparation methods, and found that the presence of boron may help to reduce catalyst deactivation during hydrotreating of heavy oil. Maritnez and Ancheyta studied the kinetics of parallel thermal and catalytic hydrotreating reactions, and identified that the reactions occur via a catalytic route at low severity reaction conditions, while thermal reactions are more favored at high severity conditions.…”
Section: Introductionmentioning
confidence: 99%